Prevalence of other associated risk factors of Cardiovascular Disease among Hypertensive patients in Eastern Nepal - Bhandari, Buna; Bhattarai, Mahesh; Bhandari, Manjul; Ghimire, Anup; Pokharel, Paras Kumar (Nepalese Heart Journal, 2014)
Background and Aims : Cardiovascular disease is the leading cause of death worldwide. Hypertension is one of the most important risk factors for Cardiovascular Diseases which cause 45% of global cardiovascular morbidity and mortality. Hypertension, along with other risk factors such as smoking, diabetes and obesity, is an emerging epidemic in many developing countries. This study aimed to find out the prevalence of other associated conventional risk factors of cardiovascular disease among hypertensive patients. Methods: Community based cross sectional study was conducted among 154 hypertensive patients over age 35yrs in Dharan Municipality. Data were collected by face to face interview method using structured questionnaire then analyzed by using descriptive and inferential statistics. Results: Around 29% hypertensive patients were between the age of 45 – 55 yrs and above 65 years. Prevalence of obesity was significantly higher 70.8%. Similarly, 46.8% had habit of taking high salt diet and 58.4% were taking high fat diet. Likewise, less physically active people were 58.4% and 64.9% were consuming alcohol regularly. Whereas 42.9% were smoker and 48.7% had stressful life. Moreover, this study also showed 46.1% had uncontrolled blood pressure in this hypertensive group. Conclusion: Cardiovascular Disease risk factors are highly prevalent among the hypertensive patients in this study. DOI: http://dx.doi.org/10.3126/njh.v11i1.10978 Nepalese Heart Journal 2014;11(1): 27-31